2001
DOI: 10.1046/j.0306-5251.2001.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

An interaction between the cytochrome P450 probe substrates chlorzoxazone (CYP2E1) and midazolam (CYP3A)

Abstract: Aims The use of multiple probe substrates to evaluate the activity of drug metabolizing enzymes requires that there are no inter±substrate interactions. As part of a series of studies to develop a clinically useful collection of probe substrates that could be given alone or in any combination, we observed an interaction between midazolam (MDZ) and another component of the six-drug cocktail. Published data indicated that the interacting component was likely to be chlorzoxazone. This was investigated as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 11 publications
2
60
0
Order By: Relevance
“…Using a combination of quinidine and rifampin with the five P450 probe substrate mixture, selective enzyme inhibition and induction of multiple enzymes were demonstrated (Branch et al, 2000). Despite these initial promising results, subsequent studies identified an interaction between chlorzoxazone (CYP2E1) and midazolam (CYP3A) (Palmer et al, 2001).…”
Section: Cocktailsmentioning
confidence: 99%
“…Using a combination of quinidine and rifampin with the five P450 probe substrate mixture, selective enzyme inhibition and induction of multiple enzymes were demonstrated (Branch et al, 2000). Despite these initial promising results, subsequent studies identified an interaction between chlorzoxazone (CYP2E1) and midazolam (CYP3A) (Palmer et al, 2001).…”
Section: Cocktailsmentioning
confidence: 99%
“…In contrast to other existing cocktails (e.g., Frye et al, 1997;Palmer et al, 2001;Blakey et al, 2004), the cocktail used here has several useful peculiarities, including semisequential midazolam administration, allowing the assessment of hepatic and intestinal CYP3A4 activity within 1 day; low doses for all substances, minimizing the risk for adverse reactions; the inclusion of optional cocktail components; and the use of fully validated metrics for all P450s included.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Here, the low-dose cocktail strategy could be shown to be an effective tool to assess the drug-drug interactions profile of propiverine in vivo. All probe substrates used in this cocktail approach have been previously shown to be enzyme-selective substrates without relevant mutual interaction in vivo (Endres et al, 1996;Frye et al, 1997;Streetman et al, 2000b;Bruce et al, 2001;Palmer et al, 2001;Wang et al, 2001;Zhu et al, 2001;Blakey et al, 2004). The composition of the cocktail used here was tailored primarily with respect to the previous information obtained in in vitro studies, suggesting that any clinically relevant interaction of propiverine with cytochrome P450 enzymes as a substrate, inhibitor, and/or inducer would mainly concern CYP3A4 and possibly also CYP2C9 and/or CYP2C19.…”
Section: Downloaded Frommentioning
confidence: 99%
“…However, the value of the cocktail approach may be limited due to marked intrasubject variability and the possibility of interaction between the coadministered probes. Palmer et al (2001) reported that chlorzoxazone significantly altered the pharmacokinetics of oral midazolam, perhaps through inhibition of first-pass metabolism by CYP3A in the intestine.…”
Section: Herb-cyp Interactions 41mentioning
confidence: 99%